Assessment of historic buildings after an earthquake using various advanced techniques. (April 2023) - Kilic, Gokhan
Abstract: Monuments are structures with historical, archaeological, and cultural qualities. They were not designed or constructed to be earthquake resistant, and so pose risks to the community and are vulnerable to collapse or irreversible damage, particularly in seismically active areas. This study conducted a condition assessment of two different historic buildings to estimate their functional life following an earthquake on Samos Island on October 30, 2020. The study combined laboratory analysis, polarized optical microscope analysis, and FTIR (Fourier Transform Infrared Spectroscopy) spectral data analysis along with advanced techniques, such as Ground Penetrating Radar (GPR), thermal imaging, and Resistivity Measurement (RM). The signal and image analyses demonstrated the successful application of an integrated approach, with implications for protecting the constructed cultural heritage for a covering both scientific maintenance and decision making.